Role of Granulosa Cells in the Aging Ovarian Landscape: A Focus on Mitochondrial and Metabolic Function - Alberico, Hannah C.; Woods, Dori C. (Frontiers in Physiology, 2022)
Mitochondria are at the intersection of aging and fertility, with research efforts centered largely on the role that these specialized organelles play in the relatively rapid decline in oocyte quality that occurs as females approach reproductive senescence. In addition to various roles in oocyte maturation, fertilization, and embryogenesis, mitochondria are critical to granulosa cell function. Herein, we provide a review of the literature pertaining to the role of mitochondria in granulosa cell function, with emphasis on how mitochondrial aging in granulosa cells may impact reproduction in female mammals.